Accounting Comparability, Audit Effort, and Audit Outcomes - Zhang, Joseph H. (Contemporary Accounting Research, 2018)
Abstract Accounting comparability among peer firms in the same industry reflects the similarity and the relatedness of firms’ operating environments and financial reporting. From the perspectives of “inherent audit risk” and “external information efficiency,” comparability is helpful for auditors in assessing client audit risk and lowers the costs of information acquisition, processing, and testing. I posit that the availability of information about comparable clients helps improve audit efficiency and accuracy. Empirical results show that comparability is negatively related to audit effort (surrogated by audit fees and audit delay). Moreover, comparability is negatively associated with the likelihood of audit opinion errors. These findings are robust to different specifications of regression models, particularly for the “endogeneity” issues due to the possible reverse causality that auditor style might influence client firms’ comparability. In sum, the study shows that accounting comparability enhances the utility of accounting information for external audits.